Does Transition to Retirement Promote Grandchild Care? Results from the Survey of Health, Ageing and Retirement in Europe - Tanskanen Antti O.; Danielsbacka Mirkka; Hämäläinen Hans; Solé-Auró Aïda (Turun yliopisto, 2022)
Grandparental child care is an important form of intergenerational support. This article explored first time whether the transition to retirement affects the amount of grandchild care that European grandparents provide to their descendants. The association between entry into retirement and grandchild care was studied using the longitudinal Survey of Health, Ageing and Retirement in Europe conducted in 16 countries and four regimes: Southern Europe, Central Europe, Northern Europe, and Eastern Europe. Data collected in five waves between 2004 and 2015 were utilized. We ran panel fixed-effect regression models, which consider individual’s variation and person-specific changes over time, providing a test for causality in the associations between retirement and grandchild care. Transition to retirement was associated with increased grandchild care among both grandmothers and grandfathers. Grandmothers more often looked after grandchildren than grandfathers, but entry into retirement increased grandchild care more among grandfathers than grandmothers. Transition to retirement was associated with increased grandchild care in all parts of Europe, but the magnitude of the effect was strongest in Southern Europe, followed by Northern Europe, Central Europe, and Eastern Europe, respectively. This study indicated that when the role conflict as grandchild caregivers and employees disappears, the amount of grandchild care older Europeans provide to their descendants increased. The fact that at retirement older adults have more time resources to provide informal family support should be carefully acknowledge in policymaking and discussions considering the societal role of older people.